The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1128/mbio.01448-20
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Communities across Global Marine Basins Show Important Compositional Similarities by Depth

Abstract: The environmental surveys following the 2010 Deepwater Horizon (DWH) spill identified a variety of hydrocarbon-degrading microorganisms, and laboratory studies with field-collected water samples then demonstrated faster-than-expected hydrocarbon biodegradation rates at 5°C. Knowledge about microbial community composition, diversity, and functional metabolic capabilities aids in understanding and predicting petroleum biodegradation by microbial communities in situ and is therefore an important component of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…Yet, Q10 remains close to 1 for all hydrocarbon fractions, demonstrating the adaptation of deep-water microbes in the Eastern Mediterranean to ambient conditions and their ability to degrade hydrocarbons at comparable, if not greater, rates to surface communities. Our results confirm findings of faster-than-expected hydrocarbon degradation rates in deep waters of the GoM following DWH [48].…”
Section: Discussionsupporting
confidence: 90%
“…Yet, Q10 remains close to 1 for all hydrocarbon fractions, demonstrating the adaptation of deep-water microbes in the Eastern Mediterranean to ambient conditions and their ability to degrade hydrocarbons at comparable, if not greater, rates to surface communities. Our results confirm findings of faster-than-expected hydrocarbon degradation rates in deep waters of the GoM following DWH [48].…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies revealed that in many systems bioremediation of crude oil can be enhanced by addition of nitrogen and phosphorus ( 17 , 63 ). While oil-degrading bacteria are found in many marine systems ( 64 ), their metabolic requirements may vary by system, depending on limitations in situ . The significant genomic dissimilarity between the strains of Colwellia and Cycloclasticus found at POLA and the ones found at the Gulf of Mexico implies that we cannot assume similarity in metabolic requirements between systems.…”
Section: Discussionmentioning
confidence: 99%
“…While 68.71% of the microbial community in Jeonglyeongchi was dominated by one species belonging to Platyhelminthes, the microbial community of Weagok and Wangdeungjae was composed of several species belonging to 3–4 phyla ( Table II ). Thus, it is believed that the similarity between microbial communities does not depend on diversity indicators ( Miller et al 2020 ; Wen et al 2020 ). Nonetheless, we support that the comparison between microbial communities should be accompanied by a composition comparison factor ( Shi et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%